Reaction of chilli (Capsicum annuum L.) genotypes and hybrids against Fusarium wilt (Fusarium solani) - R L Chavan, Y S Amaresh, T B Maruti, B V Tembhurne, (Journal of Spices and Aromatic Crops, 2014)
Field experiment was conducted to evaluate chilli (Capsicum annuum L.) genotypes and hybrids against Fusarium solani. About 56 restorer lines and 38 F1 hybrids were evaluated for resistance to Fusarium solani under laboratory conditions. Among the 56 genotypes, none of them were immune or resistant. However, only one genotype viz., P3 was found moderately resistant in both seed inoculation and rapid root dip transplanting techniques. However, out of 38, two hybrids, viz., JNA2 × ACB1 × 9608D and Rajaput × P3 showed resistance under sick pot culture condition.